Dermoid cyst of the pancreas: A rare cystic neoplasm. (2015) - Lee, Seung Eun; Choi, Yoo Shin; Hong, Soon Uk; Oh, Hyoung-Chul; Lee, Eun Sun
Highlights: We successfully resected 4.2 cm-sized cystic mass of pancreas through laparoscopic approach. Pathologic examination revealed a dermoid cyst of pancreas. Literature review showed that dermoid cysts of the pancreas are rare benign, and congenital tumors. Preoperative diagnosis is challenging, and surgical resection is the standard treatment. Abstract: Introduction: Dermoid cyst of the pancreas, also called cystic teratoma, is a benign, well-differentiated, and extremely rare germ cell neoplasm. Preoperative diagnosis is challenging since there are no definitive preoperative diagnostic tests or pathognomonic findings. Presentation of case: We report a case of a 54-year-old male who presented with an incidentally detected pancreatic cystic mass at the tail of the pancreas. Computerized tomography revealed a benign cystic mass such as oligocystic serous cystadenoma or a hemorrhagic cyst. However, a high CEA level from EUS guided aspirated fluid suggested mucinous cystic neoplasm. After laparoscopic spleen-preserving distal pancreatectomy, the final diagnosis was confirmed as a dermoid cyst of the pancreas. Conclusion: Despite the benign nature of the dermoid cyst, complete surgical resection is mostly inevitable due to the difficulty of preoperative diagnosis as in the present case.